1996
DOI: 10.3109/00498259609046736
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolism and disposition of ethoxyquin in rat and mouse. II. Metabolism

Abstract: 1. The major pathways of ethoxyquin (EQ) metabolism in both the rat and mouse are O-deethylation and conjugation to endogenous substrates. 2. The two major EQ-derived metabolites excreted in rat urine were in the form of sulphate conjugates, 1,2-dihydro-6-hydroxy-2,2,4-trimethylquinoline sulphate, and 1,2,3,4-tetrahydro-3,6-dihydroxy-4-methylene-2,2-dimethylquinoline sulphate. The latter apparently arises from an intramolecular rearrangement of the 3,4-epoxide of ethoxyquin. 3. Mouse urine contained one major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
(19 reference statements)
1
21
0
Order By: Relevance
“…Sulfotransferase activity was not measured. In rodents, saturation of sulfotransferases (SULTs) generally precedes that of UGTs (Burka et al, 1996; Hjelle and Klaassen, 1984); therefore, it can be assumed that the conjugation capacity for endogenous estrogen was compromised in the NTP study. In the present study, the gene responses for the assayed UGT and SULT isoforms were variable in tissues; however, the data indicated potential for change in the ratio of sulfation to glucuronidation after five days of treatment with 250 mg TBBPA/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfotransferase activity was not measured. In rodents, saturation of sulfotransferases (SULTs) generally precedes that of UGTs (Burka et al, 1996; Hjelle and Klaassen, 1984); therefore, it can be assumed that the conjugation capacity for endogenous estrogen was compromised in the NTP study. In the present study, the gene responses for the assayed UGT and SULT isoforms were variable in tissues; however, the data indicated potential for change in the ratio of sulfation to glucuronidation after five days of treatment with 250 mg TBBPA/kg.…”
Section: Discussionmentioning
confidence: 99%
“…EQDM administration reduced liver Cyp1a1 mRNA concentrations to less than 3% that of control rats, and Cyp2b1 mRNA was increased to 192% that of control rats. Inhibition of rat CYP activity by EQ has been reported (11,28,32), and Parke et al (42) suggested that EQ binds to CYP enzymes and thereby inhibits their activity, manifested as increased effects of the sedative hexobarbitone after a single dose of EQ. However, repeated doses of EQ produced the opposite effect, indicating an adaptive response through the induction of CYP enzymes.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, Ugt1a mRNA transcription and overall UGT activity were not different in EQDM and control rats, apparently indicating that glucoronidation is not a prevalent pathway for metabolism of EQDM. In addition to glucoronidation, large amounts of glutathione conjugates were observed in bile of rats exposed to EQ, implying that GST is involved in EQ metabolism (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations